Manajemen Implementasi Kurikulum Merdeka dalam Penguatan Pembelajaran Mendalam: Studi Literatur Sistematis - Adhistya Mahatvavirya; Dian Nur Antika Eky Hastuti (Prosiding Konferensi Ilmiah Dasar, 2026)
This study aims to synthesize dominant issues in the implementation of the Merdeka Curriculum from the perspective of educational management and to propose a curriculum management framework for strengthening deep learning in schools. This study used a systematic literature review guided by PRISMA 2020. Literature was collected from Google Scholar, Garuda, SINTA, DOAJ, ERIC, Scopus, and Crossref using Indonesian and English keywords. From 312 initial records, 30 articles published between 2021 and 2026 met the inclusion criteria and were analyzed using thematic synthesis. The findings show that Merdeka Curriculum implementation is shaped by seven major themes: curriculum leadership, teacher readiness, professional development, assessment management, resource support, monitoring and evaluation, and deep learning integration. The synthesis indicates that curriculum implementation is not merely a pedagogical issue, but an educational management issue involving leadership, coordination, teacher capacity, supervision, assessment, and continuous improvement. This study proposes an input–process–output–outcome curriculum management framework to strengthen curriculum enactment and meaningful learning. The study contributes to educational management literature by integrating curriculum implementation issues into a systematic management framework.